2020
DOI: 10.1002/osp4.418
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the development of overweight and obesity in children between 2.5 and 8 years of age: The prospective ABIS study

Abstract: Summary Background A relationship between overweight and obesity early in life and adolescence has been reported. The aim of this study was to track changes in overweight/obesity in children and to assess risk factors related to the persistence of overweight/obesity between 2.5 and 8 years. Study design Children who participated in all three follow‐ups at 2.5, 5 and 8 years in the prospective cohort All Children in Southeast Sweden (ABIS) (N = 2245, 52.1% boys and 47.9% girls) were classified as underweight, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the present study, we found that majority of the preschool-aged children remained normal weight between ages 3 and 5 years but also that those children having overweight at age of 3 mainly remained overweight at age of 5. These findings are in line with other population-based studies using BMImeasures 25,26 . Obesity at age of 3 years has been shown to predict overweight or obesity at adolescence 24 and the importance to screen and prevent obesity at preschool age is well acknowledge in other studies 23,24,31 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we found that majority of the preschool-aged children remained normal weight between ages 3 and 5 years but also that those children having overweight at age of 3 mainly remained overweight at age of 5. These findings are in line with other population-based studies using BMImeasures 25,26 . Obesity at age of 3 years has been shown to predict overweight or obesity at adolescence 24 and the importance to screen and prevent obesity at preschool age is well acknowledge in other studies 23,24,31 .…”
Section: Discussionsupporting
confidence: 92%
“…In a large population-based study, the probability of having overweight or obesity in adolescence was almost 90% for those having obesity at age of 3 years 24 . Also other population-based studies have shown that children having normal weight at early years of life remains normal weight at school age, but those children having overweight develop obesity and those having obesity remains obese [24][25][26] . However, previous data relies on BMI-measures and similar data on changes in body composition at preschool age…”
Section: Introductionmentioning
confidence: 97%
“…Obesity in childhood is likely to track into adulthood 2–4 . Longitudinal data from children born 1997–1999 in Sweden show that children with overweight or obesity at five years of age tend to remain living with overweight or obesity later in childhood 5 . However, there is also considerable new development of obesity 2,4,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported potential predictors for childhood obesity included maternal prepregnancy BMI >30 kg/m 2,10 maternal delivery BMI >30 kg/m 2,4,35 excessive gestational weight gain (>18 kg), 11-13 maternal smoking, 24,25 maternal diabetes, 15-17,38 maternal non-Caucasian ethnicity, 22,23 antenatal or perinatal antibiotics, 20,21 cesarean delivery, 18,19 LGA at birth, 17,26,29 and male sex. 22,23,27,28 We also categorized shorter duration of BF as an obesity predictor and defined this as either no BF or any duration of BF less than 6 months for this practical clinical endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, 39.8% of adults, 18.5% of youth between 2 and 19 years, and 13.9% of children between 2 and 5 years were obese in 2015-2016. 1 As a child matures, present body mass index (BMI) becomes increasingly predictive of later life BMI, 2 with half of obese adolescents having been overweight/obese since the age of 5 years. 3 Thus, preventing obesity in early childhood is critical.…”
Section: Introductionmentioning
confidence: 99%